Desain Green Data Center Pada Pt. Utac Manufacturing Services Indonesia - Syafrianto Syafrianto (SANTIKA is a scientific journal of science and technology, 2017)
The development the world of technology today is very extraordinary in helpinghuman needs, especially in the world of information. The use of computers thatare so high can cause enormous environmental effects and hazards in thesurrounding environment. Green Computing (green computer) is a step toreduce the environmental effects caused without harming the existing ecosystem.Green Computing is a computer-friendly way to use computers. The newparadigm for Data Center uses architectural design that includes processors andother devices with low power consumption and designs data centers using lowerenergy to prevent harmful effects on the environment. In this paper will bediscussed what is green data center (Green computer) and design data from thedata center proposed at PT. UTAC Manufacturing Services Indonesia